2020
DOI: 10.1088/1742-6596/1477/3/032005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Decision Tree, K-NN, Naive Bayes and SVM with MWMOTE on UCI Dataset

Abstract: Imbalanced data causes misclassification because the majority of the dominant data is in the minority data, which results in a decrease in the value of accuracy. UCI dataset is a public dataset that can be used as a dataset in machine learning. This study aims to evaluate the Decision Tree, K-NN, Naive Bayes, and Support Vector Machine classification methods on data imbalances in MWMOTE. MWMOTE is used in resolving Imbalanced cases through weighting and grouping. This goal is achieved by evaluating the Decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…Jadhav and Channe 47 , compared between decision tree, K-NN and Naïve Bayes classifier by using whether data and concluded that the accuracy of decision tree and KNN was more accurate (99%) compared to Naïve Bayes classifier which had the accuracy of 92.857%. Untoro et al 48 compared the Decision Tree, K-NN, Naive Bayes and SVM with MWMOTE on UCI Dataset and found that decision tree is an efficient process compared to K-NN, SVM and Naïve Bayes and concluded that for Decision Tree test data had an accuracy value of 94.32%, KNN of 92.67%, Support Vector Machine of 85.61%, and Naïve Bayes of 84.30%. Yadav et al 49 compared the fish abundance prediction accuracy between linear regression, neural networks and classification and regression tree (CART) models and found that NNs and CART models produced better prediction accuracy compared to LR model.…”
Section: Resultsmentioning
confidence: 99%
“…Jadhav and Channe 47 , compared between decision tree, K-NN and Naïve Bayes classifier by using whether data and concluded that the accuracy of decision tree and KNN was more accurate (99%) compared to Naïve Bayes classifier which had the accuracy of 92.857%. Untoro et al 48 compared the Decision Tree, K-NN, Naive Bayes and SVM with MWMOTE on UCI Dataset and found that decision tree is an efficient process compared to K-NN, SVM and Naïve Bayes and concluded that for Decision Tree test data had an accuracy value of 94.32%, KNN of 92.67%, Support Vector Machine of 85.61%, and Naïve Bayes of 84.30%. Yadav et al 49 compared the fish abundance prediction accuracy between linear regression, neural networks and classification and regression tree (CART) models and found that NNs and CART models produced better prediction accuracy compared to LR model.…”
Section: Resultsmentioning
confidence: 99%
“…There are many types of algorithms for classifying sentiment, one of which is Support Vector Machine (SVM) [15]. SVM in several studies achieved higher accuracy [12] [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Korade in [10] applied different machine learning techniques and compared them to identify the best suitable for the prediction of wine by selecting features. In [4] [17] investigated DT, KNN, NB, and SVM using MWMOTE (The Majority Weighted Minority Oversampling Technique). These suggestions outcomes enabled us to synthesize synthetic data more accurately while lowering the level of bias or noise.…”
Section: Related Workmentioning
confidence: 99%